COMMUNICATION SKILLS: MENINGKATKAN KEBERANIAN DAN KEPERCAYAAN DIRI MAHASISWA MELALUI PELATIHAN PUBLIC SPEAKING - Nurul Chaerani; Hasyyati Shabrina; Dini Lestari; Fauzan Fahrussiam; Andrie Ridzki Prasetyo; Musdi Musdi (Jurnal Abdi Insani, 2023)
The 4.0 revolution bring major challenges to higher education institutions in preparing curriculum relevant to demands from business, industrial, and other work-related area, to produce competent graduates. Student competencies that the working world wanted were not only hard skills but also soft skills such as adequate communication skills and public speaking skills. Nowadays, a big portion of the student body lack in confidence and courage to take part in discussion or has limited presentation skill, especially in the Forestry program University of Mataram. This problem needs to be addressed and resolved with institutional help by holding public speaking training for the students. This training was purposed to increase the courage, confidence, and skill of the students to be able to speak in front of the audience. The training processes started with a coordination process between the committee and the board of the study program, training day, and Evaluation from the participants. The participants of this training were students in the Forestry program University of Mataram from various years, and the trainers were from Fresh Radio Lombok. The training course began with a sharing session from the source person to motivate the participants and continued with a lecture about the basics of public speaking, a practice session on how to create catchy phrases for concluding occasions, sharing tips and tricks in public speaking, and ended with evaluations. The results of this training showed that this training was successful in increasing the motivation of the participants in order to elevate their ability in public speaking. The evaluation from the participants showed that the participants felt very satisfied, and rated the training process and the materials shared were very good.